Predicting durability of a disease resistance gene based on an assessment of the fitness loss and epidemiological consequences of avirulence gene mutation - Vera Cruz, Casiana M.; Bai, Jianfa; Oña, Isabelita; Leung, Hei; Nelson, Rebecca J.; Mew, T.W.; Leach, Jan E. (National Academy of Sciences, 2000)
Durability of plant disease resistance ( R ) genes may be predicted if the cost of pathogen adaptation to overcome resistance is understood. Adaptation of the bacterial blight pathogen, Xanthomonas oryzae pv. oryzae ( Xoo ), to virulence in rice is the result of the loss of pathogen avirulence gene function, but little is known about its effect on aggressiveness under field conditions. We evaluated the cost in pathogenic fitness (aggressiveness and persistence) associated with adaptation of Xoo to virulence on near-isogenic rice lines with single R genes ( Xa7 , Xa10 , and Xa4 ) at two field sites endemic for bacterial blight. Disease severity was high in all 3 years on all lines except the line with Xa7 . Of two Xoo lineages (groups of strains inferred to be clonally related based on DNA fingerprinting) detected, one, lineage C, dominated the pathogen population at both sites. All Xoo strains were virulent to Xa4 , whereas only lineage C strains were virulent to Xa10. Only a few strains of lineage C were virulent to Xa7 . Adaptation to virulence on Xa7 occurred through at least four different pathways and was associated with a reduction in aggressiveness. Loss of avirulence and reduced aggressiveness were associated with mutations at the 3′ terminus of the avrXa7 allele. Strains most aggressive to Xa7 were not detected after the second year, suggesting they were less persistent than less aggressive strains. These experiments support the prediction that Xa7 would be a durable R gene because of a fitness penalty in Xoo associated with adaptation to Xa7 .